PRAGMATIC ANALYSIS OF OCULESICS IN GULLIVER’S TRAVELS BY JONATHAN SWIFT - Khaydarova Dilnavoz Rakhimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
While gestures are daily fact of life in the real world, we frequently overlook their importance in fictional worlds. This is perhaps not surprising, for as students of language we have become so accustomed to examining the words of a text that we often fail to pay adequate critical attention to the presence of non-verbal forms of communication. Gulliver's Travels provides a compelling example of this. Gestures abound in Gulliver's Travels, yet their nature, purpose, and effects have been ignored. Far from being a mere formulaic addition to a travel narrative, they are, I believe, an essential element of the text, employed by Swift in a variety of ways. Gestures, it will be seen, are used to provide a realistic and effective means of communicating between people who do not share a common language, to de- lineate Gulliver's character, to manipulate the reader's response to Gulliver, and to implement several of Swift's philosophical themes.